2019
DOI: 10.1097/01.nep.0000000000000498
|View full text |Cite
|
Sign up to set email alerts
|

Student-Novice Nurse Preparation: Addressing Barriers in Discharge Teaching

Abstract: AIM The aim of this article was to assess how and to what degree nursing students are prepared for patient discharge teaching (DT). BACKGROUND The process of discharging patients has become more complex. Despite the expectation that nursing students will be competent in providing effective DT upon graduation, the preparation of new graduates is a problem for hospitals. METHOD A review of the literature was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The content was heavily dependent on nurses' years of working experience and speciality area of practice. Junior staff found providing transition information challenging due to their limited experience and lack of standardization of the information, as identified previously (Chidume & Pass-Ivy, 2019). Study findings confirmed those of earlier studies in that information provided at discharge was too generalized for some caregivers (Keatinge et al, 2009;Pinto et al, 2010Pinto et al, , 2015.…”
Section: Discussionsupporting
confidence: 78%
“…The content was heavily dependent on nurses' years of working experience and speciality area of practice. Junior staff found providing transition information challenging due to their limited experience and lack of standardization of the information, as identified previously (Chidume & Pass-Ivy, 2019). Study findings confirmed those of earlier studies in that information provided at discharge was too generalized for some caregivers (Keatinge et al, 2009;Pinto et al, 2010Pinto et al, , 2015.…”
Section: Discussionsupporting
confidence: 78%
“…Limited skills and knowledge on how to teach patients were mentioned as a barrier to discharge teaching. Recently graduated nurses perceived gaps in their undergraduate education regarding discharge teaching, which is common to other settings (Chidume & Pass‐Ivy, 2019). Entering the workforce, they experienced gaps between what they were taught about patient teaching principles and the opportunity to practice teaching within the constraints of the work organization.…”
Section: Discussionmentioning
confidence: 99%
“…Limited skills and knowledge on how to teach patients were mentioned as a barrier to discharge teaching. Recently graduated nurses perceived gaps in their undergraduate education regarding discharge teaching, which is common to other settings (Chidume & Pass-Ivy, 2019).…”
Section: Challenges Of Addressing Critical Implementation Determinantsmentioning
confidence: 99%
“…Learner-centered educational strategies should include simulation for students to actively participate in role-playing. According to the American Nurses Association, patient education plays a fundamental role in the nurses' scope of practice; therefore, students must be given ample opportunity to practice discharge planning (Chidume & Pass-Ivy, 2020). Simulation allows students to gain experience and confidence and to practice skills, thus alleviating students' and novice nurses' anxiety and fears while lessening the experience-complexity gap (Chidume & Pass-Ivy, 2020;Ross & Carney, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…D ischarge planning is an important component of high-quality patient teaching, and is directly related to readmission rates; novice nurses may feel inadequately prepared to participate in discharge planning due to knowledge gaps and inadequate preparation in nursing education programs (Chidume & Pass-Ivy, 2020). To achieve outcomes related to transfer of information to patients, nurses must be able to recognize and address health disparities before discharge efforts are completed (Luther et al, 2019).…”
mentioning
confidence: 99%